SCIENTIFIC AND LITERARY SERVICES OF SYED NASEERUDDIN NASEER: A RESEARCH REVIEW - Ayesha Bibi; Dr. Sohail Anwar; Dr. Muhammad Ayaz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Golrah Sharif is a school where the fountains of knowledge and wisdom spring up. This is the place where lovers of love always gather to get spiritual blessings. Golrah Sharif has the honor that the disbelievers end here. Prophethood was challenged and the word of truth and truth was raised. It was Hazrat Pir Meher Ali Shah who paid the right to be the family of Rasool ?. The descendants of Hazrat Pir Meher Ali Shah also gave ample evidence of their successorship and did not let the ongoing fountain of prosperity in this school diminish. Hazrat Pir Naseeruddin Naseer is one of the great names among the glorification of the same successors of Hazrat Pir Meher Ali Shah. Pir Naseeruddin Naseer, as a Sufi, poet, writer, researcher, historian, religious scholar, taught this school. Increased the prestige of? His scholarly and literary services are definitely a part of history. His research and compilation and spiritual education were going on when suddenly the heartbreaking news came that his soul had departed. Pir Naseeruddin Naseer Sajjada Nasheen Astana Aliya Golda Sharif was preparing to deliver the Friday sermon when suddenly he had a heart attack and he was shocked by the true Creator. Pir Naseeruddin Naseer was a comprehensive scholar, he wrote poetry in seven languages He was born in Golra Sharif, Astana, in the house of Hazrat Syed Ghulam Moinuddin Gilani Golrovi. Due to being the eye and lamp of Sadat Golra Sharif and having various personal academic and literary qualities, Syed Pir Naseeruddin Naseer also held an important position in the country of Pakistan. He was of rank. Through various channels of Pakistani newspapers, magazines, radio and television, his system of eloquence used to reach every special and general. There was nothing less. He had adopted a genius personality in his life. His grasp of Arabic and Persian was evident that eminent professors of universities and eminent scholars of religious schools sought guidance from him.